Combined thyroxine/liothyronine treatment does not improve well-being, quality of life, or cognitive function compared to thyroxine alone: a randomized controlled trial in patients with primary hypothyroidism - Walsh, John P; Shiels, Lauren; Lim, Ee Mun; Bhagat, Chotoo I; Ward, Lynley C; Stuckey, Bronwyn G A; Dhaliwal, Satvinder S; Chew, Gerard T; Bhagat, Minoti C; Cussons, Andrea J (The journal of clinical endocrinology and metabolism, 2003)
T(4) is standard treatment for hypothyroidism. A recent study reported that combined T(4)/liothyronine (T(3)) treatment improved well-being and cognitive function compared with T(4) alone. We conducted a double-blind, randomized, controlled trial with a crossover design in 110 patients (101 completers) with primary hypothyroidism in which liothyronine 10 micro g was substituted for 50 micro g of the patients' usual T(4) dose. No significant (P < 0.05) difference between T(4) and combined T(4)/T(3) treatment was demonstrated on cognitive function, quality of life scores, Thyroid Symptom Questionnaire scores, subjective satisfaction with treatment, or eight of 10 visual analog scales assessing symptoms. For the General Health Questionnaire-28 and visual analog scales assessing anxiety and nausea, scores were significantly (P < 0.05) worse for combined treatment than for T(4) alone. Serum TSH was lower during T(4) treatment than during combined T(4)/T(3) treatment (mean +/- SEM, 1.5 +/- 0.2 vs. 3.1 +/- 0.2 mU/liter; P < 0.001), a potentially confounding factor; however, subgroup analysis of subjects with comparable serum TSH concentrations during each treatment showed no benefit from combined treatment compared with T(4) alone. We conclude that in the doses used in this study, combined T(4)/T(3) treatment does not improve well-being, cognitive function, or quality of life compared with T(4) alone.